Serum Metabolic Profiles of Chinese Women With Perimenopausal Obesity Explored by the Untargeted Metabolomics Approach - Ding, Shanshan; Chen, Mingyi; Liao, Ying; Chen, Qiliang; Lin, Xuejuan; Chen, Shujiao; Chai, Yujuan; Li, Candong; Asakawa, Tetsuya (Frontiers in Endocrinology, 2021)
By far, no study was focused on observing the metabolomic profiles in perimenopause-related obesity. This study attempted to identify the metabolic characteristics of subjects with perimenopause obesity (PO). Total 39 perimenopausal Chinese women, of whom, 21 with PO and 18 without obesity (PN), were recruited in this study. A conventional ultra-high performance liquid chromatography-quadrupole time-of-flight/mass spectrometry (UHPLC-QTOF/MS) followed by principal component analysis (PCA) and orthogonal partial least-squares discriminant analysis (OPLS-DA) was employed as untargeted metabolomics approaches to explore the serum metabolic profiles. Kyoto Encyclopedia of Genes and Genomes (KEGG) and MetaboAnalyst were employed to identify the related metabolic pathways. A total of 46 differential metabolites, along with 7 metabolic pathways relevant to PO were identified, which belonged to lipid, amino acids, carbohydrates, and organic acids. As for amino acids, we found a significant increase in L-arginine and D-ornithine in the positive ion (POS) mode and L-leucine, L-valine, L-tyrosine, and N-acetyl-L-tyrosine in the negative ion (NEG) mode and a significant decrease in L-proline in the POS mode of the PO group. We also found phosphatidylcholine (PC) (16:0/16:0), palmitic acid, and myristic acid, which are associated with the significant upregulation of lipid metabolism. Moreover, the serum indole lactic acid and indoleacetic acid were upregulated in the NEG mode. With respects to the metabolic pathways, the D-arginine and D-ornithine metabolisms and the arginine and proline metabolism pathways in POS mode were the most dominant PO-related pathways. The changes of metabolisms of lipid, amino acids, and indoleacetic acid provided a pathophysiological scenario for Chinese women with PO. We believe the findings of this study are helpful for clinicians to take measures to prevent the women with PO from developing severe incurable obesity-related complications, such as cardiovascular disease and stroke.